Student-Generated Advertisements as Cultural Texts: Advancing Intercultural Communicative Competence in Business Communication Pedagogy - Shafi, Saheeh (Yayasan Centre for Studying and Milieu Development of Indonesia (CESMiD), 2025)
This study investigates how student-generated online advertisements function as cultural texts for developing intercultural communicative competence (ICC) in Bangladeshi business communication courses. Guided by Ertay and Gilanlioglu’s ICC scale, social semiotics, and the notion of asynchronous interculturality, a sequential explanatory mixed-methods design was employed. In the quantitative phase (N = 90), an adapted ICC questionnaire (α = 0.89) and instructor rubrics assessed three conditions: case studies, ad creation only, and ad creation with an ICC rubric. Results showed significant differences across ICC dimensions (F(3,268) = 45.71, p < .001), with attitude improving most and awareness least. Longitudinal rubric scores confirmed large gains in language appropriateness and cultural-symbol accuracy, while visual cues improved modestly. Qualitative data from interviews, focus groups, journals, and artefact analysis highlighted students’ enthusiasm for creative tasks but also revealed an “awareness–attitude paradox,” the emotional labour of cultural mediation, and the need for explicit guidance in visual literacy. Findings demonstrate that student-generated advertisements are effective tools for advancing ICC when paired with structured assessment and reflective scaffolding. The study recommends integrating validated rubrics, visual-literacy modules, and telecollaborative exchanges into business-English curricula. Limitations include the single-institution context and short intervention period, suggesting the need for broader and longitudinal replication.